2018
DOI: 10.30682/nm1801d
|View full text |Cite
|
Sign up to set email alerts
|

The Spillover Effect of Imported Inputs on Broiler Prices in Turkey

Abstract: The broiler sector in Turkey has advanced particularly in recent years. Hence, it

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…In Turkey, production costs are the most important factors affecting the market price of chicken meat [9] . A study reports that a 10 percent increase in the price of soybean used in the poultry sector results in a 3.84 percent increase in the price of chicken meat in Turkey, and that the price of chicken meat and the prices of electricity and soybean are in an equilibrium relationship [7] . A study concerning the prices of chicken meat reported that a 50 percent decrease in the price of corn in China resulted in a 32 percent decrease in the price of chicken, whereas a 50 percent decrease in the price of soy flour resulted in a 16 percent decrease in the price of chicken [38] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Turkey, production costs are the most important factors affecting the market price of chicken meat [9] . A study reports that a 10 percent increase in the price of soybean used in the poultry sector results in a 3.84 percent increase in the price of chicken meat in Turkey, and that the price of chicken meat and the prices of electricity and soybean are in an equilibrium relationship [7] . A study concerning the prices of chicken meat reported that a 50 percent decrease in the price of corn in China resulted in a 32 percent decrease in the price of chicken, whereas a 50 percent decrease in the price of soy flour resulted in a 16 percent decrease in the price of chicken [38] .…”
Section: Discussionmentioning
confidence: 99%
“…Chicken meat prices showed an increase of 214.24%, beef prices increased 273.80% and mutton prices increased by 349.59% [3] . As chicken meat is more affordable than red meat, consumers considerably shift their preferences to chicken meat when the price of red meat increases [4][5][6][7] . The major reason for this is that chicken meat and red meat are substitute goods [1] .…”
Section: Introductionmentioning
confidence: 99%
“…In 1970s, poultry businesses in Turkey were family run business with high costs and limited production capacities, but this changed with the large investments in the industry in 1990s and 2000s, resulting in high standards of quality (Çakı, 2007). With state subsidies and planning, the poultry industry in Turkey has become one of the strongest and most rapidly developing industries in the country (Keskin and Demirbaş, 2012;Avcıoğlu et al, 2013;Karadavut and Taşkın, 2014;Çınar and Keskin, 2018). Turkey, in turn, has become one of the top ten countries that produce and export chicken (FAO, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Results indicate that there is a volatility spillover from the corn and barley market to the wheat market. Cinar and Keskin (2018) have analyzed the spillover effect on prices of imported energy and soybean that are widely used to determine broiler prices in the Turkish market. They have used the Vector Error Correction Model (VECM).…”
Section: Introductionmentioning
confidence: 99%